2021
DOI: 10.1177/03000605211036845
|View full text |Cite
|
Sign up to set email alerts
|

The NLRP3 inflammasome mediates liver failure by activating procaspase-1 and pro-IL-1 β and regulating downstream CD40-CD40L signaling

Abstract: Objectives In this prospective case–control study, we explored the regulatory roles of the NLRP3 inflammasome in hepatitis B virus-associated acute-on-chronic liver failure (HBV-ACLF). Methods Thirty patients with HBV-ACLF, 30 patients with chronic hepatitis B, and 30 healthy individuals were enrolled. Real-time reverse transcription polymerase chain reaction was used to assess mRNA levels in peripheral blood mononuclear cells and serum protein levels were assessed by enzyme-linked immunosorbent assay. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…In contrast, hepatitis B c antigen (HBcAg) promotes LPS-induced NLRP3 inflammasome activation and IL-1β production ( Wang et al, 2019 ). At last, the counteraction turns out to be the upregulation of IL-1β found in the serum, peripheral blood mononuclear cells (PBMCs) and in vitro culture primary human hepatocytes ( Tian et al, 2019 ; Zhang Z. et al, 2020 ; Li and Jiang, 2021 ). Besides, IL-1β is also linked to IFN-α treatment response.…”
Section: Cytokines In Hepatitis B Virus Infectionmentioning
confidence: 99%
“…In contrast, hepatitis B c antigen (HBcAg) promotes LPS-induced NLRP3 inflammasome activation and IL-1β production ( Wang et al, 2019 ). At last, the counteraction turns out to be the upregulation of IL-1β found in the serum, peripheral blood mononuclear cells (PBMCs) and in vitro culture primary human hepatocytes ( Tian et al, 2019 ; Zhang Z. et al, 2020 ; Li and Jiang, 2021 ). Besides, IL-1β is also linked to IFN-α treatment response.…”
Section: Cytokines In Hepatitis B Virus Infectionmentioning
confidence: 99%
“…HEV genotypes 3 and 4 caused increased IL-1β levels in rabbits, and HEV particles activated NLRP3 in primary macrophages and macrophage cell lines 67 . Patients with HBV-associated acute liver failure demonstrated increased expression of NLRP3 mRNA levels in their peripheral blood mononuclear cells 68 …”
Section: Concepts Of Inflammation In Chronic Liver Diseasesmentioning
confidence: 98%
“…[67] Patients with HBV-associated acute liver failure demonstrated increased expression of NLRP3 mRNA levels in their peripheral blood mononuclear cells. [68] Antagonizing NLRP3 function might appear as a potent anti-inflammatory strategy. Loss of murine NLRP3 ameliorates diet-induced steatohepatitis, whereas NLRP3 inflammasome gain of function worsens liver disease leading to severe fibrosis.…”
Section: Inflammasomes In Liver Inflammationmentioning
confidence: 99%
“…For example, it has been found that the levels of NLRP3 are low in normal liver tissues; however, activation of the NLRP3 inflammasome is implicated in hepatic injury. The NLRP3 inflammasome mediates liver failure by sensitizing procaspase-1 and pro-IL-1 β in HBV-related acute-on-chronic liver failure (ACLF) ( 95 , 96 ). To date, the molecular mechanisms associated with virus-mediated sensitization of the NLRP3 inflammasome have not been well examined.…”
Section: Function Of Hbx In Nlr-mediated Signaling Pathwaysmentioning
confidence: 99%